A new digital meshed polygon method for demonstrating individuality in fingerprints from different individuals - Kelana, Aslaha Musafir (Universiti Sains Malaysia, 2016)
A fingerprint produces an oriented texture pattern which represent a symbol of individuality. Until today, individuality remains scientifically unprovable and yet, none have ever been able to provide a contradicted proof to ban the theory. Be it probabilistic, statistic or mathematic. This study aims to propose a novel method to demonstrate fingerprint individuality. This is a pilot study design and a correlational study as a whole. Adobe® Photoshop® software was used to analyse fingerprint samples. For each fingerprint impression, 12 precise points were located upon the minutiae, each point was connected to construct a polygon which had produced a meshed polygon. The shape of the meshed polygon for high impression and normal impression were superimposed from a common source finger. Whereas, for meshed polygon originating from different source fingers, 20 meshed polygons from each finger type were superimposed. The result shows that for the superimposition of high impression print and normal impression print from common source finger, the shapes remained the same but differ in size, the variations are in the measurement of maximum height, breadth and area. Majority of the difference in maximum height and breadth bad a range of 0 0.05 cm only, in which, none had exceeded the threshold value 0.07 cm. Whereas, the 20 superimposed meshed polygon outlines for each finger type, had showed that none of 20 the meshed polygon outlines produced a 'match'. Hence, in order to demonstrate the individuality of fingerprint, visual evidence based on the morphology basis was shown through the constructed meshed polygons had fulfilled the requirements in producing a method to enl1anced the element of individuality.